Numerical Solution of Navier-Stokes Equations in a Two-Dimensional Complex Domain - Mateeva-Collins, E.I. (Engineering Transactions, 1977)
The paper is devoted to the numerical solution of the Navier-Stokes equations in the case of plane motion when the area for which we are seeking the solution can be distributed over adjacent to rectangles. For the rectangles one can find the "partial" solutions by the A. A. Dorodnitzyn method, from which one can construct the solution for the whole area. Numerical examples of the application of this method are given.